Associated long-term effects of decabromodiphenyl ethane on the gut microbial profiles and metabolic homeostasis in Sprague-Dawley rat offspring - Guoxia Zhang; Fengmin Ma; Ziwei Zhang; Zenghua Qi; Meiqiong Luo; Yingxin Yu (Environment International, 2023)
Decabromodiphenyl ethane (DBDPE) as a widely used brominated flame retardant is harmful to human health due to its toxicity, including cardiovascular toxicity, reproductive toxicity, and hepatotoxicity. However, the knowledge of the long-term effects and structural and metabolic function influence on gut microbiota from DBDPE exposure remains limited. This study was mainly aimed at the gut microbiome and fecal metabolome of female rats and their offspring exposed to DBDPE in early life. 16S rRNA gene sequencing demonstrated that maternal DBDPE exposure could increase the α-diversity of gut microbiota in immature offspring while decreasing the abundance of Bifidobacterium, Clostridium, Muribaculum, Escherichia, and Lactobacillus in adult offspring. The nonmetric multidimensional scaling showed a consistency in the alternation of β-diversity between pregnant rats and their adult offspring. Furthermore, the short-chain fatty acids produced by gut microbiota dramatically increased in adult offspring after maternal DBDPE exposure, revealing that DBDPE treatment disrupted the gut microbial compositions and altered the gut community's metabolic functions. Untargeted metabolomics identified 41 differential metabolites and seven metabolic pathways between adult offspring from various groups. Targeted metabolomic showed that maternal high dose DBDPE exposure obviously decreased the level of glutathione, taurine, and l-carnitine in their adult offspring, which verified the correlation between weight loss and amino acid metabolites. An interesting link between some gut bacteria (especially the Firmicutes) and fecal metabolites demonstrated the shifts in gut microbiota may drive the metabolic process of fecal metabolites. The current findings provide new insight into long-term effects on human health.